Risk Management Analysis In PT. XYZ Construction Project National Strategic Development Project - Dhevito, Ervis (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to analyze the hazard aspects affecting the project, the level of risk, and to evaluate the effectiveness of risk control in the construction project of PT XYZ (Dam Construction Project). The data used in this research was obtained from the HIRADC documents provided by the company supervisor, with a descriptive method through a case study approach. The results of this study show that risk management plays a crucial role in ensuring the smooth implementation of the project. This research is driven by the need to identify, map, and evaluate various risks that may hinder the project's progress, as well as to develop appropriate mitigation strategies. The recommendations of this study suggest that the company should strengthen the monitoring and evaluation system in a structured and sustainable manner, so that mitigation efforts can be better monitored and adjusted if necessary. Additionally, enhancing the capacity of human resources, both through training of workers and strengthening the risk management team, is an essential step in supporting the implementation of more effective mitigation strategies.